A review on dietary approaches to enhance calcium intake among adolescents - M., Chandana; Hiremath, Netravati; Sairam , Sudha (International Journal Of Community Medicine And Public Health, 2024)
Adolescence is one of the most important milestones in the life cycle stages, in which each individual undergoes various physiological and psychological changes. This period is considered one of the important stages of nutritional vulnerability. Calcium needs are elevated due to intensive bone and muscular development. Calcium acts as one of the vital minerals for bone mineralization during childhood and adolescence that primarily needs to be driven through adequate dietary sources. Globally, calcium intake in all age groups including adolescents has lowered due to changing food patterns which have highly tilted towards a high intake of ultra-processed foods. This review draws attention to enhanced calcium intake through healthy dietary measures.